2020
DOI: 10.1097/nor.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Smartphone App Reminder on Adherence to Aspirin Prescribed as Antithrombotic Therapy

Abstract: BACKGROUND: Many patients are discharged with aspirin (ASA) as an anticoagulant after joint replacement surgery. In studies in which ASA was prescribed, doses were frequently missed. Adherence to postoperative ASA regimen is critical to preventing thrombotic complications. This randomized controlled study evaluated the impact of an existing medication adherence smartphone application (app) on adherence to twice daily ASA 81 mg for 35 days after knee or hip arthroplasty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…van Dijk-Huisman et al conducted a randomized controlled trial of 97 patients undergoing TJA and found that patients who used a smartphone app with an accelerometer in addition to standard physical therapy stood and walked for 28 minutes longer on postoperative day 1 compared with patients who received standard physical therapy alone 38 . Wittig-Wells et al reported that a medication-adherence smartphone app could lead to higher medication adherence in their randomized controlled trial of 195 TJA patients 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…van Dijk-Huisman et al conducted a randomized controlled trial of 97 patients undergoing TJA and found that patients who used a smartphone app with an accelerometer in addition to standard physical therapy stood and walked for 28 minutes longer on postoperative day 1 compared with patients who received standard physical therapy alone 38 . Wittig-Wells et al reported that a medication-adherence smartphone app could lead to higher medication adherence in their randomized controlled trial of 195 TJA patients 39 .…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [31][32][33][34][36][37][38][39] showed that electronic adjuncts may impart some benefit to TJA patients. Day et al conducted a prospective study of 34 patients undergoing THA or TKA who received mobile phone messages regarding activity and pain-control reminders starting 1 week prior to surgery until 2 weeks after surgery 31 .…”
Section: Electronic Adjuncts To Physical Therapymentioning
confidence: 99%
“…Wittig-Wells et al [ 29 ] described results from a prospective open-label trial evaluating the effects of a mobile app with reminders on adherence to antiplatelet therapy in patients after hip or knee alloplasty. There were 195 patients enrolled, and 122 completed the pill count at the end of the follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the use of new technologies such as mobile applications as one of the influential factors in promoting medication self‐efficacy. 43 , 44 Achieving the same results, despite the use of different tools as well as variety of interventions and methods of using the smartphone capabilities, can be attributed to the fact that the information technology and internet advances as well as numerous advantages such as easy access, availability at any time and place, communication and information transfer capability, 45 facilitate the learning process, and improve the information satisfaction, as one of the factors affecting patient satisfaction is the teaching method. 46 Thus, as learning enhances, patients receive more information about their disease and can participate effectively in their treatment course.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Park et al's 42 also supported the effectiveness of mobile‐based education in promoting adherence to antiplatelet drug therapy during the 30 days of vulnerability after myocardial infarction or percutaneous coronary interventions. Previous studies showed that the use of new technologies such as mobile applications as one of the influential factors in promoting medication self‐efficacy 43,44 . Achieving the same results, despite the use of different tools as well as variety of interventions and methods of using the smartphone capabilities, can be attributed to the fact that the information technology and internet advances as well as numerous advantages such as easy access, availability at any time and place, communication and information transfer capability, 45 facilitate the learning process, and improve the information satisfaction, as one of the factors affecting patient satisfaction is the teaching method 46 .…”
Section: Discussionmentioning
confidence: 99%